Perancangan Prototipe Alat Pendeteksi Banjir berbasis esp32 dan IoT di Perumahan Tridaya Indah Bekasi - Fahmi Al Ashri; Pandapotan Kristian Sitorus; Naufal Ilham Ramadhan; Danendra Ganijan Sunarso; Susilawati, M.Si (Peneliti.net, 2026)
Flooding is a serious and recurring problem in the Tridaya Indah Housing complex, Bekasi. Delays in information and emergency response often exacerbate the disaster's impact. This research aims to design an Internet of Things (IoT) based prototype for a flood early warning system (EWS) and mitigation. The research method used is Prototyping, which includes the stages of requirements gathering, design, prototype building, evaluation, and iteration. This system integrates an ESP32 microcontroller as the main processing unit, a JSN-SR04T ultrasonic sensor for water level detection, a flame sensor for secondary hazard (fire) detection, a buzzer as a local alarm, and a relay-controlled mini water pump for automatic mitigation. Remote monitoring and real-time notifications are implemented using the Blynk platform via a smartphone application. The black-box testing results show that the prototype functions 100% as designed. The system successfully differentiated three condition levels (Safe, Alert, Danger) accurately, and successfully activated the buzzer and water pump when the